2020
DOI: 10.1101/2020.08.26.268573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embryo CHH hypermethylation is mediated by RdDM and is autonomously directed inBrassica rapa

Abstract: Background: RNA directed DNA methylation (RdDM) initiates cytosine methylation in all contexts, and maintains asymmetric CHH methylation (where H is any base other than G). Mature plant embryos show one of the highest levels of CHH methylation, and it has been suggested that RdDM is responsible for this hypermethylation. Because loss of RdDM in Brassica rapa causes seed abortion, embryo methylation might play a role in seed development. RdDM is required in the maternal sporophyte, suggesting that small RNAs fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…Newly detected zygote siRNAs mark future CHH hypermethylation sites in mature embryos Hypermethylation of embryo has been reported in a number of angiosperm species, including Arabidopsis, soybean, chickpea, Brassica rapa, and rice (Bouyer et al, 2017;Chakraborty et al, 2020;Kawakatsu et al, 2017;Li et al, 2020b;Lin et al, 2017;Rajkumar et al, 2020;Zhou et al, 2021). We found that newly detected siRNA loci have abundant CHH methylation in embryos that is dependent on the RdDM methyltransferase DRM2 (Fig 5C).…”
Section: A Special Class Of Highly Abundant Maternal Sirnas Persists In the Zygotesupporting
confidence: 54%
“…Newly detected zygote siRNAs mark future CHH hypermethylation sites in mature embryos Hypermethylation of embryo has been reported in a number of angiosperm species, including Arabidopsis, soybean, chickpea, Brassica rapa, and rice (Bouyer et al, 2017;Chakraborty et al, 2020;Kawakatsu et al, 2017;Li et al, 2020b;Lin et al, 2017;Rajkumar et al, 2020;Zhou et al, 2021). We found that newly detected siRNA loci have abundant CHH methylation in embryos that is dependent on the RdDM methyltransferase DRM2 (Fig 5C).…”
Section: A Special Class Of Highly Abundant Maternal Sirnas Persists In the Zygotesupporting
confidence: 54%
“…Whether embryonic siRNAs were generated in situ by the embryo, or transported from endosperm or the surrounding seed coat has not been resolved, nor has their function fully elucidated (Bouyer et al 2017;Grover et al 2020;Kirkbride et al 2019;Chakraborty et al 2021). Of note, in Brassica rapa, maternal sporophytic RdDM, but not zygotic RdDM, is required for seed viability, showing that at least in this species, parental siRNA contributions are important for seed development, though maternal sporophyte RdDM was not sufficient to drive embryo hypermethylation (Chakraborty et al 2021;Grover et al 2020). The overlap between embRdDM loci and DME targets may reflect communication between embryo, endosperm and/or the seed coat, due to their intimate development within the seed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CHH methylation is dramatically increased upon cell-cycle arrest in vegetative nuclei, mature embryos and columella root caps 5,14,17 . Progressive CHH hypermethylation correlates with reduced cell cycle activity during embryogenesis 14 , but loss of embryonic CHH hypermethylation did not cause observable developmental defects 18,19 . Upon seed germination, cell-cycle activities increase while CHH methylation decreases 20 .…”
Section: Meiosismentioning
confidence: 97%